Effect of a physical exercise program on plasma concentration of adiponectin in overweight and obese children (Research, Society and Development, 2022)
Adiponectin is considered a biomarker of health status, and high levels are associated with good health. Science discusses the results on the effects of physical activity on increasing adiponectin levels, especially in child with obesity. The scope of the present study was to evaluate a physical exercise intervention program, after 10 months of duration, in the plasma concentration of adiponectin in students from six to nine years of age with overweight and obesity. This is a randomized clinical study of a near-experimental intervention of the type before and after. The physical exercise resulted in a significant reduction in the percentage of body fat (%BF) and triglycerides. Adiponectin there was a non-significant increase. The present study showed that the practice of physical exercise did not increase adiponectin levels, but was responsible for a great improvement in the children lipid profile and reduction in %BF.